2014
DOI: 10.3846/16487788.2014.926643
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the Icao Training Institute Into the International Education Network

Abstract: Abstract. Training plays a crucial role in ensuring the development and implementation of international Standards and Recommended Practices in aviation activities. Considering the existing policies and practices, the experts agreed on seven principles that the pan-European training policy should follow: promoting training, developing competency-based training, establishing an aviation culture, fostering mutual recognition, anticipating needs, supporting competition in training, ensuring quality of training and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…In following up with the above scenario, according to Kulyk (2014) Therefore, in order to sustain the retraining initiative, it will be imperative for them to expand their workforce and infrastructure accordingly. According to an interview performed in April 2011 with Captain Steve Jones, a former Chief Pilot and operation manager of United Airlines, it was found that the average pilot-to-aircraft ratio is 6.5.…”
Section: Training Standards Proposalmentioning
confidence: 99%
“…In following up with the above scenario, according to Kulyk (2014) Therefore, in order to sustain the retraining initiative, it will be imperative for them to expand their workforce and infrastructure accordingly. According to an interview performed in April 2011 with Captain Steve Jones, a former Chief Pilot and operation manager of United Airlines, it was found that the average pilot-to-aircraft ratio is 6.5.…”
Section: Training Standards Proposalmentioning
confidence: 99%
“…Learning materials, both theoretical and practical, is taken from two parts. The first part is from AC 65-02, which refers to the International Civil Aviation Organization (ICAO) Annexes 1 (Kulyk and Suslova, 2014) and the second one refers to the standard knowledge of aviation electronics (avionics). For the courses, the curriculum using the standard module of EASA part 66 (Usanmaz, 2011) is selected for training aircraft maintenance technicians.…”
Section: Fig 2 References In the Program Implementation Of Amto 147 mentioning
confidence: 99%
“…The sphere of the subjective analysis entropy paradigm (Kasianov, 2013;Kasianov, Goncharenko, 2015, 2017Goncharenko, 2017) encompasses aspects of training and education of aviation specialists (Kulyk & Suslova, 2014), decision support in air navigation (Shmelova, Sikirda, Rizun, Salem, & Kovalyov, 2017) as well as the flight support operational radio systems (Solomentsev, Zaliskyi, & Zuiev, 2016).…”
Section: Introductionmentioning
confidence: 99%